2022
DOI: 10.4103/jfmpc.jfmpc_115_22
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of menopausal symptoms among women in Vadodara, Central Gujarat: The urban-rural divide

Abstract: Aim: The aim of this article is to estimate prevalence of menopausal symptoms among women in the menopausal age group and study the urban-rural differences. Methods and Design: Analytical cross-sectional study conducted in rural and urban field practice areas of a tertiary care center affiliated to Medical College, where 290 women (145 each from urban and rural areas) were interviewed to measure prevalence of menopausal symptoms. Forty-one symptoms were divided into ‘Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Symptoms experienced during menopause include vasomotor, psychosomatic, and psychological symptoms (Augoulea et al, 2019;Hazlina et al, 2022;Sood et al, 2019;Yadav et al, 2021). Shringarpure et al (2022) found the results of a study of 145 women in urban and rural areas, most of them experienced psychosomatic symptoms such as physical exhaustion-fatigue, sleep problems, difficulty climbing stairs, hot flushes, and body aches.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms experienced during menopause include vasomotor, psychosomatic, and psychological symptoms (Augoulea et al, 2019;Hazlina et al, 2022;Sood et al, 2019;Yadav et al, 2021). Shringarpure et al (2022) found the results of a study of 145 women in urban and rural areas, most of them experienced psychosomatic symptoms such as physical exhaustion-fatigue, sleep problems, difficulty climbing stairs, hot flushes, and body aches.…”
Section: Introductionmentioning
confidence: 99%